Demystifying risk attitudes and fertilizer use: A review focusing on the behavioral factors associated with agricultural nitrogen emissions in South Asia - Begho, Toritseju; Eory, Vera; Glenk, Klaus (Frontiers in Sustainable Food Systems, 2022)
Fertilizer use is environmentally unsustainable in South Asia. Ideally, farmers would follow optimal fertilization rates for crops based on scientific recommendations. However, there is ample evidence on why farmers under-fertilize or over-fertilize their crops. Important amongst them is that farmers' attitude to risk influences decisions on fertilizer use. This paper reviews studies on the effects of risk attitude on fertilizer use, the timing of application, and application intensity. We observe that the use of fertilizer is affected by perceptions of fertilizer as a risk-enhancing or risk-reducing input. In order to influence the future fertilizer decisions of farmers, several policy measures are suggested. Among these, gradual withdrawal of fertilizer subsidies, repurposing subsides toward improved technologies that increase productivity, improves nitrogen use efficiency (NUE) and reduce emission, providing enhanced-efficiency fertilizers and eliminating the fraudulent practice of fertilizer adulteration may be the most appropriate in a South Asian context.